Об одной геометрической модели временных параллельных процессов - Ошевская, Е.С, (Інститут програмних систем НАН України, 2004)
The intention of the paper is to study geometric properties of timed concurrent processes. First, we introduce a notion of timed higher dimentional transition sistems and then we provide a category-theoretic characterization of bisimulation equivalence in the context of the model under consideration.